KINERJA KEPALA KAMPUNG DALAM PENYELENGGARAAN PEMERINTAHAN DAN PEMBANGUNAN DESA DI KAMPUNG NDUMA DISTRIK MAPNDUMA KABUPATEN NDUGA - Karunggu, Nola; Rompas, Welson Yappi; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: Act. 32 of 2004 stated that the village chief has a fundamental duty held government affairs and communitydevelopment. PP. 72 of 2005 explains, is the task of government affairs, among others, community living arrangements inaccordance with the authority of the village. Affairs, among others, is to coordinate the development of participatoryvillage. The purpose of this study was to determine how the village head Nduma performance in governance and ruraldevelopment.This study used a descriptive-qualitative method. Informants of this study as many as 15 peoplewere taken from the employed several elements of village government officials, BPD / MTT, LPM, PKK leaders /community leaders / traditional / religious., And citizens. The main instrument in this study is a researcher himself, whilecollecting data using interview techniques and assisted with the observation danstudi dokmentasi. Data analysis was doneby using qualitative descriptive analysis-interactive model ofMilesand Hubernann.The results of the study provide conclusions: (1) Performance Nduma kampug head in the administration ofgovernment affairs villages (such as lead organization of village administration, village life setting, rulemaking village,the formation of village social institutions, peace and public order pemerliharaan village, village financial management,and services to the public) is not optimal, but generally are good enough; (2) Performance Nduma village heads in theimplementation of rural development / village (ie the coordination and facilitation of development planning,pengkoordinasikan implementation of development programs, and the mobilization and development of communityparticipation in development), also have not been up but has shown good performance.Based on the conclusions, it is recommended suggestion that the performance of the head of the village Ndumain governance and development needs to be improved and enhanced. Uutuk the village heads need to improve knowledgeand skills dang governance and development.Keywords: village head performance, governance and rural development.